2014
DOI: 10.5796/electrochemistry.82.865
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Confined Polymer Structure on Proton Transport Property in Sulfonated Polyimide Thin Films

Abstract: The organized structure and proton transport property in sulfonated polyimide (SPI) thin film have been studied, much less is known at the interfacial charge transport during confinement of such materials. The proton conductivity of SPI thin film is correlated well with the highly oriented polymer structures as determined by infrared (IR) p-polarized multiple-angle incidence resolution spectrometry (p-MAIRS) and in situ RH dependent synchrotron grazing incidence X-ray diffraction (GI-XRD). The high proton cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Because this spectroscopic method is an infrared spectroscopic method, it is useful because it is applicable to non-crystalline materials. In combination with X-ray scattering technique, it is useful to discuss the structure of crystalline and amorphous parts in other materials [43,44,47,48,[52][53][54]. It also makes it possible to discuss the substrate dependence in greater detail [25,36,37] or casting solvent dependence [43,54] of the interfacial structure.…”
Section: Introductionmentioning
confidence: 99%
“…Because this spectroscopic method is an infrared spectroscopic method, it is useful because it is applicable to non-crystalline materials. In combination with X-ray scattering technique, it is useful to discuss the structure of crystalline and amorphous parts in other materials [43,44,47,48,[52][53][54]. It also makes it possible to discuss the substrate dependence in greater detail [25,36,37] or casting solvent dependence [43,54] of the interfacial structure.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve high proton conductivity of polymer electrolytes, various polymer electrolyte membranes such as perfluorosulfonated polymers, sulfonated block copolymers, and graft copolymers have been examined based on a concept of the well phase-separated hydrophilic channels composed of hydrophobic backbones and hydrophilic parts. The proton conductivity of polymer electrolyte membranes is closely related to several parameters such as acidity, number of sulfonic acid groups, main chain and side chain structures, and membrane morphology. From a different perspective, structural confinement effects of polymer electrolyte thin films have been reported. Structure and transport properties in confined polymer thin films differ drastically from those of the bulk materials because of interactions between the polymer and substrate surface. , For example, a study of Nafion thin films demonstrated that the degree of the phase segregation, water uptake, and proton conductivity decreased concomitantly with decreasing film thickness. ,, …”
Section: Introductionmentioning
confidence: 99%
“…As consequence, the chain alignment in thin films on a substrate surface can also be controlled by film casting solvents in low RH. In the previous reports, [14][15][16] the proton conduction path had not been discussed because of the less ordered structure. In this study, the pMAIRS study enables us to discuss the molecular orientation in the non-ordered parts.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] The confinements in thin films induce preferred chain packings and molecular orientations along the in-plane or out-of-plane direction from a substrate plane by self-assembly, which exhibits the highly organized ion-conducting channels that possibly lead to the change of transport characteristics. [14][15][16][17][18][19] Therefore, the organized structure has attracted considerable interest for high proton conduction in thin films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation